Prospective multicentre trials in developing countries: Willingness of surgeons to participate - (:unkn) unknown (SCANDINAVIAN UNIVERSITY PRESS, 1998)
Objective: To assess the feasibility of conducting a multicentre study among surgeons in Turkey. Design: Prospective open multicentre study. Setting: Teaching hospitals in Turkey. Subjects: Surgeons working in 23 university and 15 state hospitals. Interventions: Surgeons willing to participate were asked to look for the presence of Meckel's diverticulum in all patients undergoing laparotomy. Main outcome measures: To find out the number of surgeons willing to participate in the study and once they agreed to see how they fulfilled the requirements. Results: 14 agreed to participate (12 from universities and 2 from state hospitals) and completed the study. A total of 2781 patient records were collected. University hospitals were more willing to participate than state hospitals (52% compared with 13%) but state hospitals contributed 20% of the patients. The number of patients contributed in the first and second halves of the study did not differ, reflecting no diminution of the enthusiasm. Conclusion: This study, with no financial support, showed that it is possible to conduct multicentre studies among surgeons in developing countries such as Turkey. Increased awareness of the importance of publication may have helped to obtain this result.